2017
DOI: 10.1103/physrevb.95.014511
|View full text |Cite
|
Sign up to set email alerts
|

Phase stability and large in-plane resistivity anisotropy in the 112-type iron-based superconductor Ca1xLaxFeAs2

Abstract: The recently discovered high-Tc superconductor Ca1−xLaxFeAs2 is a unique compound not only because of its low symmetry crystal structure, but also because of its electronic structure which hosts Dirac-like metallic bands resulting from (spacer) zig-zag As chains. We present a comprehensive first principles theoretical study of the electronic and crystal structures of Ca1−xLaxFeAs2. After discussing the connection between the crystal structure of the 112 family, which Ca1−xLaxFeAs2 is a member of, with the othe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 75 publications
2
20
0
Order By: Relevance
“…This reaction is found by GGA to be CaAs + FeAs → CaFeAs 2 . The onsite Coulomb interaction U = 5 eV and Hund's coupling constant J = 0.8 eV were used in the Gutzwiller calculations 158,178 . We found that CaFeAs 2 lies 7 meV/atom above the hull.…”
Section: Fe 112 Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction is found by GGA to be CaAs + FeAs → CaFeAs 2 . The onsite Coulomb interaction U = 5 eV and Hund's coupling constant J = 0.8 eV were used in the Gutzwiller calculations 158,178 . We found that CaFeAs 2 lies 7 meV/atom above the hull.…”
Section: Fe 112 Compoundsmentioning
confidence: 99%
“…88 La 0.12 Fe(As 0.9 Sb 0.1 ) Tc vs anion height in iron pnictide and chalcogenide superconductors. Adapted from Ref 178…”
mentioning
confidence: 99%
“…1c). For known IBSC, the apparent correlation between the anion (As, Se, and others) height from the iron layer and the superconducting critical temperature was already reported [88]. Figure 4 shows the critical temperature T c for several IBSC in relation to the distance between anions and Fe layers using data presented in Ref.…”
Section: Superconducting Propertiesmentioning
confidence: 66%
“…Figure 4 shows the critical temperature T c for several IBSC in relation to the distance between anions and Fe layers using data presented in Ref. [88]. We supplemented this plot by the new data for K122 at zero and 30 GPa pressures (blue open circles in Fig.…”
Section: Superconducting Propertiesmentioning
confidence: 99%
See 1 more Smart Citation